Literacia informacional e processo formativo: desafios aos profissionais da informação - Silva, Armando Malheiro da (2016)
In the Information Age, where we are increasingly immersed in, the operative concepts of Informational Literacy (LI) and Digital Inclusion (DI) prove to be strategic and essential for understanding what can go the information behavior of children, youth and adults, in an space complex, global and intensely saturated by media and sources of information / knowledge. They are also important if we want to deepen and place, today and in prospect analysis, the scientific and professional training in the documentation and information area. To this end, we return in this communication, the polyhedral model of training of information professionals, presented at the 8th Congress BAD (2004), and rethinking it, taking into account some results of the Research Project eLit.pt. We evoke the eLit.pt model as a theoretical and practical intervention tool that enabling enhance critical skills (L.I.), at the level of secondary education and at university / polytechnic, without which the skills, listed in the standards and references requirements, will not intentional unlikely to be well treated by those for whom they are supposed to have.